The integration of the molecular methods in the diagnosis algorithm for the poliovirus detection in the sewage water: comparing concentration and detection methods. A Pilot Study - Băicuş Anda (Sciendo, 2017)
Introduction. Two cases of circulating vaccine-derived poliovirus type 1(cVDPV1), from southwestern Ukraine, bordering Romania, were confirmed in 2015 and the environmental enterovirus surveillance was enhanced in our country. The molecular detection of human enteroviruses as a screening test followed by isolation on cell culture lines or sequencing could be proposed as a new diagnosis algorithm.